An Unusual Clinical Presentation of Budd–Chiari Syndrome in an Adolescent Boy - Agrawal, Shreyash; Pathania, Garima; Mittal, Richa; Mehndiratta, Sumit; Singh, Amitabh (Journal of Child Science, 2022)
We report an unusual case of massive splenomegaly with pancytopenia without ascites, which was referred to us with suspicion of a myeloproliferative disorder in an adolescent boy. The work-up done was noncontributory to a hematological disorder. On further work-up, liver biopsy depicted sinusoidal congestion, with Doppler study suggestive of nonvisualization of hepatic veins. There was hypertrophy of the right lobe and the presence of venovenous collaterals. Janus kinase 2 (JAK2) V617F mutation was negative, which confirmed the absence of unidentified myeloproliferative disorder. This was an atypical presentation of Budd–Chiari syndrome (BCS) in children. The absence of ascites could be due to more efficient collateral formation in adolescent age groups due to angiogenesis. Underlying thrombophilia was detected as methylenetetrahydrofolate reductase mutation 677C > T with raised serum homocysteine levels. It is imperative to be aware of the diverse clinical manifestations in children for early detection and appropriate intervention to prevent catastrophic results in pediatric BCS.
Keywords: Budd–Chiari syndrome; hypersplenism; myeloproliferative disorder; children; thrombophilia